Health Literacy and Health Service Use in Germany - Eva-Maria Berens; Dominique Vogt; Kristin Ganahl; Heide Weishaar; Jürgen Pelikan; Doris Schaeffer (SLACK Incorporated, 2018)
Background: Health literacy (HL) is defined as the ability to process health-related information to make decisions to maintain health and improve quality of life. A growing number of studies demonstrate that people with lower HL are less likely to use preventive services but more likely to use curative, emergency, or hospital care. Objective: This study investigated the relationship between HL and the use of different types of health services in a sample of the general German population, as we expected that the effect of HL on the frequency of use differs by type of health service. Methods: A nationally representative sample of 2,000 people in Germany was interviewed in person in 2014. Analyses of the data included frequencies of contacts with doctors, other health professionals, hospitals, and emergency services. Analysis also included a HL measure (European Health Literacy Survey Questionnaire), as well as sociodemographic and health status indicators. To test whether and how HL is related to the frequency of use of the different types of curative health services, regression analyses were performed. Key Results: Respondents with lower HL scores reported more frequent use of all four included types of curative health services. Although multiple regression analysis showed a direct significant effect of HL only on doctor (β = −.066) and other health professionals visits (β = −.103), no significant direct effect of HL on hospital and emergency services use was found when sociodemographic and health-related factors were controlled for. Conclusions: Health professionals should be aware that their patients are likely to have difficulties in understanding and processing health-related information. Interventions to strengthen HL should aim at improving health care literacy and, moreover, not only address individuals but also consider demands related to the health care system and health professionals' communication skills.